RELASI PARASOSIAL DAN KOMUNIKASI DUA ARAH DALAM LIVE STREAMING STUDI NETNOGRAFI PADA LIVE STREAMING YOUTUBE DEANKT - Sabila Asoka Saharani; Kuwatono (PT Wahana Global Education, 2025)
The rapid development of digital technology has transformed the landscape of mass communication and social interaction, particularly through live streaming platforms like YouTube. This research focuses on the digital interactions and communication patterns between streamer Aldean Tegar Gemilang (Deankt) and his community, #WEAREMEMBERSHIP. It examines the parasocial relationships that emerge through interactive features such as live chat, Super Chat, and donations. Utilizing qualitative methods, including participatory observation, content analysis, and in-depth interviews, this study explores Deankt's verbal and non-verbal communication strategies for fostering emotional closeness despite the inherently one-sided nature of these relationships. The findings highlight the evolution of parasocial interactions within Indonesia's unique social-cultural context and reinforce the role of interactive media in forming new social bonds. This study contributes both theoretically and practically to our understanding of modern digital communication and offers strategies for building loyal audience communities.